Eksplorasi Nilai Kearifan Lokal Sebagai Dasar Pengembangan Teori Kesantunan Berbahasa Indonesia - Agung Pramujiono (Universitas PGRI Adi Buana Surabaya, 2015)
The theory of Politeness in general oriented to the theory developed by western experts as Lakoff, Leech, Brown and Levinson, Arndt and Janncy, and Watts.